The Classroom Discourse Observation Protocol (CDOP): A quantitative method for characterizing teacher discourse moves in undergraduate STEM learning environments - Kranzfelder, Petra (PLoS One, 2019)
We describe the development and validation of a new instrument, the Classroom Discourse Observation Protocol (CDOP), which quantifies teacher discourse moves (TDMs) from observational data in undergraduate STEM classrooms. TDMs can be conceptualized as epistemic tools that can mediate classroom discussions. Through an inductive–deductive coding process, we identified commonly occurring TDMs among a group of biology instructors (n = 13, 37 class session) teaching in Active Learning Environments. We describe the CDOP coding scheme and its associated matrix that allows observers to reliably characterize TDMs in 2-min time intervals over the course of a class period. We present the protocol, discuss how it differs from existing classroom observation protocols, and describe the process by which it was developed and validated. Also, we show how this protocol is able to discriminate the discursive practices of instructors teaching in undergraduate STEM learning environments with sample qualitative and quantitative results that illustrate its utility for assessing and improving STEM instructional practices.